Handbook of public administration - Rabin, Jack; Hildreth, W. Bartley; Miller, Gerald (Boca Raton : CRC/Taylor & Francis, 2007)
This handbook includes entirely new chapters on information technology and conduct of inquiry. It covers the major areas of public administration in a single, concise reference.
Includes bibliographical references and index.
osa 06/06/13
Loans
Keywords: Public administration